PlGF/FLT-1 deficiency leads to reduced STAT3-C/EBPβ signaling and aberrant polarization in decidual macrophages during early spontaneous abortion - Chang, Ruiqi; Dai, Jingcong; Wang, Li; Liu, Hao; Jiang, Huanhuan; Liu, Xiaoyu; Jiang, Linying; He, Fan; Hu, Lina (Frontiers in Immunology, 2023)
Dysregulated macrophage polarization (excessive M1-like or limited M2-like macrophages) in the early decidua contributes to allogeneic fetal rejection and thus early spontaneous abortion. However, the modulators of M1/M2 balance at the maternal-fetal interface remain mostly unknown. In this study, placental growth factor (PlGF) was found to drive the M2-like polarization of decidual macrophages (dMφs) from normal pregnant women and the downregulation of PlGF/Fms-like-tyrosine-kinase receptor 1 (FLT-1) in human early decidua may result in spontaneous abortion. Moreover, the CBA/J×DBA/2 abortion-prone mice displayed a lower FLT-1 expression in uterine macrophages than did CBA/J×BALB/c control pregnant mice. After recombinant human PlGF (rhPlGF) treatment, dMφs exhibited a higher expression of CD209 and IL-10, a lower expression of CD86, an increased tyrosine phosphorylation level of STAT3, and a higher expression of CEBPB. These effects of rhPlGF on dMφs were nearly abrogated by AG490, a selective inhibitor of STAT3. Furthermore, the CEBPB promoter luciferase activity in dMφs was upregulated by STAT3 overexpression, which was almost blocked by the mutations of the CEBPB promoter in its predicted binding site to STAT3. These findings were further supported by a higher embryo resorption rate in Pgf knockout mice, in addition to the reduced IL-10 production, STAT3 transcription, and C/EBPβ expression in uterine macrophages. In conclusion, PlGF plays a key role in early pregnancy maintenance by skewing dMφs toward an M2-like phenotype via the FLT-1-STAT3-C/EBPβ signaling pathway. Excitingly, our results highlight a rationale that PlGF is a promising target to prevent early spontaneous abortion.